2015
DOI: 10.1117/12.2193832
|View full text |Cite
|
Sign up to set email alerts
|

Towards high dynamic range extensions of HEVC: subjective evaluation of potential coding technologies

Abstract: This paper reports the details and results of the subjective evaluations conducted at EPFL to evaluate the responses to the Call for Evidence (CfE) for High Dynamic Range (HDR) and Wide Color Gamut (WCG) Video Coding issued by Moving Picture Experts Group (MPEG). The CfE on HDR/WCG Video Coding aims to explore whether the coding efficiency and/or the functionality of the current version of HEVC standard can be significantly improved for HDR and WCG content. In total, nine submissions, five for Category 1 and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 4 publications
0
30
3
Order By: Relevance
“…Narwaria et al [15] found that HDR-VQM was performing significantly better than HDR-VDP-2 for both video and still image content. However, our results show that both metrics have similar performance, while it was reported in [9] that HDR-VQM performs lower than HDR-VDP-2 for HDR video compression. The divergence between these findings might be due to the contents and types of artifacts considered in the different studies.…”
Section: Best Performing Metricscontrasting
confidence: 44%
See 3 more Smart Citations
“…Narwaria et al [15] found that HDR-VQM was performing significantly better than HDR-VDP-2 for both video and still image content. However, our results show that both metrics have similar performance, while it was reported in [9] that HDR-VQM performs lower than HDR-VDP-2 for HDR video compression. The divergence between these findings might be due to the contents and types of artifacts considered in the different studies.…”
Section: Best Performing Metricscontrasting
confidence: 44%
“…Finally, Narwaria et al [15] have reported that their HDR-VQM metric performs similar or slightly better than HDR-VDP-2 for HDR image quality assessment. Regarding HDR video quality assessment, four studies were also reported by Azimi et al [27], Rerabek et al [28], Hanhart et al [9], and Narwaria et al [15]. The authors of [15] found that HDR-VQM is the best metric, far beyond HDR-VDP-2, in contradiction to the findings of [9], which showed lower performance for HDR-VQM when compared to HDR-VDP-2.…”
Section: Introductioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Recently, Hanhart et al [17] conducted an evaluation of nine HDR video compression algorithms submitted in response to the Motion Pictures Experts Group (MPEG) committee's Call for Evidence (CfE) [25] to evaluate the feasibility of supporting HDR and Wide Color Gamut (WCG) content using the High Efficiency Video Codec (HEVC) [43] encoder. The paper concludes that the proposals submitted to MPEG can noticeably improve the standard HDR video coding technology and QA metrics such as PSNR-DE1000, HDR-VDP2 and PSNR-Lx can reliably detect visible difference.…”
Section: Evaluation Of Hdr Video Compression Methodsmentioning
confidence: 99%